(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In the present era, the threat of enemies plays an important role in security policies of any state. In this perspective, military soldiers play an important and vital role. There are several considerations concerning the security of those troopers. So, for the security purpose of troopers, several equipment or devices are attached with them to take the look on their health status and their ammunitions. Health related sensors like pulse rate sensor, body temperature measuring sensor, weather updsates, emergency buttons data transmission and processing capabilities, can thus help to make low-cost wearable solutions for health monitoring. GPS is used for basically point the latitude and longitude to find exact location of soldier. WIFI module can be used for effective range of high-speed transmission that will be required to relay information on situational awareness, tactical instructions, and covert surveillance related data during special operations reconnaissance and other missions. So, by using these equipment’s we are trying to implement the basic life guarding system for soldiers at a low cost and high reliability.